Analisis Keyakinan Tentang Matematika Dan Pengetahuan Konten Pedagogik Matematika Calon Guru Matematika - Muhyidin, Kholil; Ekawati, Rooselyna; Sofro, A'yunin (Universitas Dr. Soetomo, 2022)
Abstract This study aims to determine whether there is a relationship between beliefs about mathematics and mathematics pedagogical content knowledge possessed by mathematics teachers on the ratio material and explanations of prospective teachers' mathematics pedagogic content based on the beliefs about mathematics drawn. This research used by Mixed Method. With a sample of 31 students who took micro teaching courses. from the sample, each subject who has a view on instrumentalist, platonic, and problem-solving mathematics is selected. Data were collected by presenting beliefs, mathematics pedagogical content knowledge tests, and interviews. Statistical data analysis by using rank-spearman correlation test. The results of research showed that there was no relationship between beliefs about mathematics and mathematics pedagogical content knowledge of prospective mathematics teachers. Prospective teachers mathematics who have a view of instrumentalist and problem solving mastered almost all indicators that exist in the component of mathematics pedagogical content knowledge. Meanwhile, prospective teachers mathematics who have a view of platonic have almost not mastered all the indicators that exist in the component of mathematics pedagogical content knowledge.